Hybrid organizations : new business models for environmental leadership - Boyd, Brewster (Greenleaf Publishing, 2009)
This book offers a glimpse into the future. The companies it describes are pioneers, the first-movers in market shifts that will eventually become mainstream. These "hybrid organizations"--Or what others call "values-driven" or "mission-driven" organizations -- operate in the blurry space between the for-profit and non-profit worlds. They are redefining their supply chains, their sources of capital, their very purpose for being; and in the process they are changing the market for others. Using a combination of high-level survey analysis and, more importantly, in-depth executive interviews, the book helps fill the present gap in literature on environmentally focused and financially driven for-profit businesses. Moreover, it highlights key trends and critical themes that enable this new wave of socially conscious and fiscally minded enterprises to be successful in meeting both sets of goals.